If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5a + -3)(5a + -3) = 0 Reorder the terms: (-3 + 5a)(5a + -3) = 0 Reorder the terms: (-3 + 5a)(-3 + 5a) = 0 Multiply (-3 + 5a) * (-3 + 5a) (-3(-3 + 5a) + 5a * (-3 + 5a)) = 0 ((-3 * -3 + 5a * -3) + 5a * (-3 + 5a)) = 0 ((9 + -15a) + 5a * (-3 + 5a)) = 0 (9 + -15a + (-3 * 5a + 5a * 5a)) = 0 (9 + -15a + (-15a + 25a2)) = 0 Combine like terms: -15a + -15a = -30a (9 + -30a + 25a2) = 0 Solving 9 + -30a + 25a2 = 0 Solving for variable 'a'. Factor a trinomial. (3 + -5a)(3 + -5a) = 0Subproblem 1
Set the factor '(3 + -5a)' equal to zero and attempt to solve: Simplifying 3 + -5a = 0 Solving 3 + -5a = 0 Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -5a = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -5a = 0 + -3 -5a = 0 + -3 Combine like terms: 0 + -3 = -3 -5a = -3 Divide each side by '-5'. a = 0.6 Simplifying a = 0.6Subproblem 2
Set the factor '(3 + -5a)' equal to zero and attempt to solve: Simplifying 3 + -5a = 0 Solving 3 + -5a = 0 Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -5a = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -5a = 0 + -3 -5a = 0 + -3 Combine like terms: 0 + -3 = -3 -5a = -3 Divide each side by '-5'. a = 0.6 Simplifying a = 0.6Solution
a = {0.6, 0.6}
| 2x/x-9-x/2(x-9)= | | 3(2x-5)-(x+3)=(2x+1)+4 | | 7=10-3u | | 5a-2=3a+4 | | 2(x-4)+12=x-4(6+2x)+9x | | 12×-1/3 | | 13=10 | | 3log(2)x=28 | | -53/4-31/2= | | 4x-40=13-6x+3 | | 2y-10x=10 | | 3.50x=10.50 | | 3x^2+10=100 | | 2x+7=15+4x | | 2x+12+9=x+3 | | 6x+5+9x-10+80+90=360 | | X+6=-8x+5 | | (x^2+0.8)(x^2+0.8)= | | 3x-29=17-5x | | 18=9+3h | | 7tanx+2=9 | | 3y+6-2=8-2y | | 7/3*8/6 | | -4/7y16 | | 12=15-3p | | 2(x-4)+12=x-4(6+2x)+9 | | 42r^2-35r=0 | | -5+1y=-8x | | 15=2v+3 | | 9p-4q=-15 | | 8=10-2r | | -6x+3=-6x-5 |